2014
DOI: 10.1007/978-3-642-40609-6_14
|View full text |Cite
|
Sign up to set email alerts
|

Molecule-Based Magnetic Coolers: Measurement, Design and Application

Abstract: Abstract. The recent progress in molecule-based magnetic materials exhibiting a large magnetocaloric effect at liquid-helium temperatures is reviewed. The experimental methods for the characterization of this phenomenon are described. Theory and examples are presented with the aim of identifying those parameters to be addressed for improving the design of new refrigerants belonging to this class of materials. Advanced applications and future perspectives are also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…Magnetocaloric effect, consisting in dependence of entropy on the applied magnetic field, bears high potential for modern applications and attracts rising attention within the community of condensed matter physicists [43,44]. Therefore, one of the highly interesting challenges for physics of molecular magnets is characterization of their magnetocaloric properties and constant search for optimization of the magnetocaloric performance [45][46][47][48][49][50][51][52][53]. Experimental studies focused on such qualities have been reported for some classes of systems, to mention Febased systems [54,55] or Mn-based ones [55][56][57] as well as molecules incorporating Gd [58].…”
Section: Introductionmentioning
confidence: 99%
“…Magnetocaloric effect, consisting in dependence of entropy on the applied magnetic field, bears high potential for modern applications and attracts rising attention within the community of condensed matter physicists [43,44]. Therefore, one of the highly interesting challenges for physics of molecular magnets is characterization of their magnetocaloric properties and constant search for optimization of the magnetocaloric performance [45][46][47][48][49][50][51][52][53]. Experimental studies focused on such qualities have been reported for some classes of systems, to mention Febased systems [54,55] or Mn-based ones [55][56][57] as well as molecules incorporating Gd [58].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the possible multifunctionality of molecular magnets [11] opens the way towards numerous applications. Among them, the magnetic cooling based on the magnetocaloric effect (MCE) should be emphasized as particularly interesting application [12][13][14][15]. MCE [16] consists in the dependence of the entropy of substance on the external magnetic field and thus allows designing of a thermodynamic cycle for refrigeration (working between two constant temperatures) or outlining the procedure used to lower the temperature [17].…”
Section: Introductionmentioning
confidence: 99%
“…Frequency-dependent out-of-phase (χ′′M) ac susceptibility signals for Zn6Dy6 in a 3 G oscillating field 55. …”
mentioning
confidence: 99%